The Internationalization of Chinese Companies: Are the Traditional Resource Based Theories Valid Yet? - Adele PARMENTOLA (Revista de Management Comparat International)
Over the past two decades, Chinese multinationals have made a huge amount of foreign direct investment abroad, making China the largest outward investor among top ten emerging countries. Nevertheless only in the last years some authors have begun to study this phenomenon.. According to these considerations, aim of this paper is to analyse the recent phenomenon of the internationalisation of Chinese firms in order to verify if it offers an opportunity to extend the traditional internationalisation theories based on the experience of developed countries’ firms. Combining the results obtained describing the international process of two large Chinese companies with the assumptions of the Resource based View approach and the Uppsala model, the paper shows that traditional proposed internationalisation theories cannot explain the internationalisation of Chinese firms. The international development of Chinese firms cannot be described as a gradual process direct toward near markets and aimed to exploit existing resources and to accumulate experiential knowledge. Chinese firms are forced to go abroad in order to gain the immaterial resources necessary to compete in the home and in the foreign market. The analysis of the Chinese firms’ internationalisation process seems to be an opportunity for extending the traditional internationalisation theories.